The Zimbabwe miracle - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Zimbabwe's agricultural success over recent years has been heralded as a good example of how modern farming methods can be made to work even under Africa's traditional subsistence farmers working communally-owned land using low or no-input shifting...